2021
DOI: 10.1016/j.rsma.2020.101566
|View full text |Cite
|
Sign up to set email alerts
|

Incidence of 49 elements in the blood and scute tissues of nesting hawksbill turtles (Eretmochelys imbricata) in Holbox Island

Abstract: Due to progressive urban development along the Mexican Caribbean coastline, it is crucial to gauge the impact of anthropogenic contamination of marine ecosystems through biomonitoring procedures.In the current study, we quantified the concentration of 49 inorganic elements in the blood and scute tissues of clinically healthy nesting hawksbill sea turtles (Eretmochelys imbricata). The elements were classified into four groups: Group A: essential mineral elements with toxic potential; Group B: non-essential elem… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
2
2

Year Published

2022
2022
2023
2023

Publication Types

Select...
2
2

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 36 publications
0
2
2
Order By: Relevance
“…Although high concentrations can be toxic and cause neurological and dermal damage and decreased sea turtle hatching success [ 14 , 66 , 67 ]. The concentrations identified in this study were lower than those reported in other species of sea turtles worldwide [ 14 , 34 , 68 , 69 ].…”
Section: Resultscontrasting
confidence: 86%
See 1 more Smart Citation
“…Although high concentrations can be toxic and cause neurological and dermal damage and decreased sea turtle hatching success [ 14 , 66 , 67 ]. The concentrations identified in this study were lower than those reported in other species of sea turtles worldwide [ 14 , 34 , 68 , 69 ].…”
Section: Resultscontrasting
confidence: 86%
“…Previous studies have shown that the distribution of essential and toxic elements in sea turtle blood presents higher levels of essential elements than toxic ones [62,69,70]. This distribution may be affected when intoxication or pathological responses occur; for example, a study in Brazil reported higher concentrations of Pb compared to Zn and Cu in C. mydas when these turtles presented fibropapillomatosis [50].…”
Section: Plos Onementioning
confidence: 99%
“…We found the Hg levels were in a similar range for all studied species, except in E. imbricata which presented very low concentrations. Although our results for this single individual cannot be extrapolated to the species level, similarly low Hg levels have been previously reported in scutes of E. imbricata (Escobedo-Mondragón et al 2021, 2023. E. imbricata forage on a low trophic level, mainly on sponges, but also on other reef-encrusting organisms (Bjorndal 1997) which may or may not contain low Hg concentrations (e.g., Orani et al 2020 for sponges, and Rizzini et al 2016).…”
Section: Discussionsupporting
confidence: 79%
“…Although high concentrations can be toxic and cause neurological and dermal damage and decreased sea turtle hatching success [11,70,71]. The concentrations identified in this study were lower than those reported in other species of sea turtles worldwide [11,13,72,73].…”
Section: Resultscontrasting
confidence: 55%
“…Previous studies have shown that the distribution of metals in sea turtle blood presents higher levels of essential elements than toxic ones [66, 73, 74]. This distribution may be affected when intoxication or pathological responses occur; for example, a study in Brazil reported higher concentrations of Pb compared to Zn and Cu in C. mydas when these turtles presented fibropapillomatosis [53].…”
Section: Resultsmentioning
confidence: 99%